Modelling the Errors of EIA’s Oil Prices and Production Forecasts by the Grey Markov Model - Gholam Hossein Hasantash; Hamidreza Mostafaei; Shaghayegh Kordnoori (International Journal of Economics and Financial Issues, 2012)
Grey theory is about systematic analysis of limited information. The Grey-Markov model can improve the accuracy of forecast range in the random fluctuating data sequence. In this paper, we employed this model in energy system. The average errors of Energy Information Administrations predictions for world oil price and domestic crude oil production from 1982 to 2007 and from 1985 to 2008 respectively were used as two forecasted examples. We showed that the proposed Grey-Markov model can improve the forecast accuracy of original Grey forecast model.